Petroleum geology of the Irish Sea and adjacent areas - Meadows, N. S. (The Geological Society, 1997)
This text provides a snap-shot of current understanding on the petroleum geology of the East Irish Sea and adjacent areas.
Keywords: Basins (Geology) -- Irish Sea.; Petroleum -- Geology -- Irish Sea.; elektronické knihy; electronic books